THE COMPETENCY–BASED CURRICULUM OF ENGLISH SUBJECT FOR SENIOR HIGH SCHOOL IN INDONESIA: A CRITICAL EVALUATION - Harits Masduqi (ISSN)
The Indonesian government has nationally implemented the competency–based curriculum of English subject for senior high school in Indonesia since 2004. The recent curriculum has been warmly welcomed by teachers as it is claimed that the curriculum will be more effective in enhancing the teaching learning process than the previous curricula. Some problems, however, may potentially hinder the implementation of the latest curriculum. If these problems remain unsolved, Indonesian people will end up repeating the same failure of the previous curricula: teaching learning process that is far from communicative competence. Therefore, it is recommended that the newest curriculum should be modified based on the importance of competent teachers and authentic resources, communicative situations for grammar mastery, and ongoing assessment.